Cervical Spinal Chondrosarcoma: A Rare Case Report - Saha , Shuvro; Halder, Rathin; Khan, Uzzal Kumer Sadhu; Hoque, Saiful; Ahmed, Salah Uddin; Intiser, Sakib (Journal of Shaheed Suhrawardy Medical College, 2024)
Cervical spinal chondrosarcoma is an exclusively uncommon disease. A 35-year-old man presented with a history of swelling on the right side of the back of the neck for 1 year and night pain with numbness of the right upper limb for 6 months. Magnetic Resonance Imaging of the cervical spine showed a 7.8×4.5 cm extendible mass lesion involving the spinous process and lamina of the C5-C7 vertebrae. The tumor was excised without stabilization of the cervical spine. After one year of follow-up, the patient is disease-free, and the cervical spine is stabilized with normal movements. A good prognosis is seen when wide excision is done in the case of low-grade chondrosarcoma, even though it is deep-seated. J Shaheed Suhrawardy Med Coll 2022; 14(2): 66-68